Concurrent Myotonic Dystrophy and Inflammatory Myopathy in a Patient with HIV/AIDS. (20th May 2021) - Gupta, Akash; Huttner, Anita; Azar, Marwan M.
Abstract : Neuromuscular complications are common in patients with HIV/AIDS at any stage of the disease process. Myopathies can be secondary to antiretroviral therapy, HIV myositis itself, or other etiologies. Here, we present the case of a middle-aged male with HIV who presented with myalgias and was diagnosed with myotonic dystrophy and HIV-associated polymyositis after extensive workup including clinical history and physical exam, laboratory markers, electromyogram, and muscle biopsy. This case illustrates the importance of a comprehensive workup for myopathy in HIV/AIDS and the possibility of multiple concurrent conditions.